The effect of job satisfaction, workplace spirituality and organizational commitment on work productivity with organizational citizenship behavior (OCB) as intervening variable (Case study on Bank Muamalat Indonesia KC Solo) - Musalim Ridlo; Ifan Arin Wardahana; Kristiani Gracelia Jessica (Journal of Business & Banking, 2020)
The study aims to identify and analyze the influence of job satisfaction, organizational commitment, workplace spirituality on work productivity with Organizational Citizenship Behavior (OCB) as an intervening variable. The population of this study consists of all employees of Muamalat Bank Solo Branch. The data were collected by a questionnaire distributed to 40 employees of Muamalat Bank Solo Branch. This study uses a saturated sample technique or total sampling. The data were analyzed using multiple linear testing and path analysis. The results show that job satisfaction and Organizational Citizenship Behavior (OCB) have a positive and significant effect on employee work productivity, while spirituality at work and organizational commitment has a positive but not significant effect on employee productivity. Simultaneously, it shows that job satisfaction, workplace spirituality, organizational commitment and Organizational Citizenship Behavior (OCB) have a positive and significant effect on employee work productivity. Based on the path analysis test,  job satisfaction, workplace spirituality and organizational commitment have a positive and significant effect on employee work productivity through Organizational Citizenship Behavior (OCB) as an intervening variable.